The Dark Holds No Terror: an Urge For Confrontation: Examining Gender Inequality in Shashi Deshpande's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The very article aims at interpreting Shashi Deshpande’snovels – The Dark Holds No Terrors from the feminist perspective. It won’t bewrong to claim that most of Indian novels which deal with woman’s issues offervarious problems pertaining to women and end up glorifying the stereotypicalvirtues, like devotion, patience and meek acceptance of whatever is meted outto a women. Women, who constitute a half of the world’s population, are nottreated equally with men. They are made to suffer meekly in a male dominatedsociety. Women are supposed to behave as their parents and husbands demand.They are not expected to give their opinions on several issues.